Characterization of dual bacteriocins producing Bacillus subtilis SC3.7 isolated from fermented food. (15th January 2022) - Epparti, Pramila; Eligar, Sachin M.; Sattur, Avinash P.; Gnanesh Kumar, B.S.; Halami, Prakash M.
Abstract: The thermostable antimicrobial peptide with broad-spectrum inhibitory activity is of great interest due to its potential application as a biopreservative agent. In the present study, we characterized a Bacillus spp. isolated from fermented foods of Northeast region, India. The selective screening of bacteriocins producers was carried out using B. subtilis based whole-cell biosensors BSF2470 and BS168.BS2. Among 12 isolates showing bacteriocin production, culture with high antibacterial activity was subjected to whole-genome sequencing and referred to as B. subtilis strain SC3.7. Through genome annotation, two bacteriocin genes spa S and sbo A, responsible for the synthesis of sublichenin and subtilosin A were identified. Further, mass spectrometric analysis confirmed the secretion of sublichenin (3346 Da), its succinylated form (3446 Da), and subtilosin A (3399 Da). Interestingly, a unique acyclic variant of subtilosin A (3417 Da) was also determined. The purified peptides were effective against various indicator strains at lower concentrations. Overall, the study reports a B. subtilis strain that produces two bacteriocins sublichenin and subtilosin A. This new combination of bacteriocins can be an effective biopreservative in the food industry. Highlights: Bacteriocin producing Bacillus spp. were screened from fermented foods. Whole genome sequence of a selected strain confirmed B. subtilis SC3.7 Exhibited wider antibacterial activity with sboA, spa S bacteriocin genes. MS analysis confirmed the production of sublichenin and subtilosin A. Succinylated isoform of sublichenin and acyclic form of subtilosin A were identified.